The event structure of perception verbs - Gisborne, Nikolas, 1966- (Oxford : Oxford University Press, 2010)
This study examines the semantics and syntactic behaviour of perception verbs such as look, see, taste, hear, feel, sound and listen. It considers their meanings, modality, and irregularity, and examines the kinds of polysemy they exhibit. It offers new insights on lexical causation, evidentiality, and processes of cognition.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Grammar, Comparative and general -- Verb